2018
DOI: 10.3390/ijms19030677
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IgG in Arthritis: Disease Pathways and Therapeutic Avenues

Abstract: Rheumatoid arthritis (RA) is a polygenic and multifactorial syndrome. Many complex immunological and genetic interactions are involved in the final outcome of the clinical disease. Autoantibodies (rheumatoid factors, anti-citrullinated peptide/protein antibodies) are present in RA patients’ sera for a long time before the onset of clinical disease. Prior to arthritis onset, in the autoantibody response, epitope spreading, avidity maturation, and changes towards a pro-inflammatory Fc glycosylation phenotype occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 195 publications
0
17
0
Order By: Relevance
“…Autoantibodies after binding to their target antigens trigger downstream inflammatory cascades either directly or in the form of immune complexes [26]. At this effector phase of arthritis, activation of different pathways of complement [27,28] and FcγR-bearing immune cells contributes to cartilage destruction either directly or by promoting the secretion of inflammatory cytokines and matrix lysing enzymes ( Figure 2) [29]. At the same time, antibodies binding to collagen type II (CII) can also induce target damage independent of inflammatory mediators or cells [30].…”
Section: B Cells and Autoantibodiesmentioning
confidence: 99%
“…Autoantibodies after binding to their target antigens trigger downstream inflammatory cascades either directly or in the form of immune complexes [26]. At this effector phase of arthritis, activation of different pathways of complement [27,28] and FcγR-bearing immune cells contributes to cartilage destruction either directly or by promoting the secretion of inflammatory cytokines and matrix lysing enzymes ( Figure 2) [29]. At the same time, antibodies binding to collagen type II (CII) can also induce target damage independent of inflammatory mediators or cells [30].…”
Section: B Cells and Autoantibodiesmentioning
confidence: 99%
“…Currently, immunoglobulins and Fc fragments are used in the treatment of certain diseases, for example, thrombocytopenic purpura (ITP) [118], rheumatoid arthritis [119], and nephrotoxic nephritis [120]. A study of Fc glycosylation in inflammatory arthritis, ITP, and epidermolysis of bullosa acquisita (EBA) models showed that when sialic acid was removed from Fc fragments, it made IVIg unable to exhibit anti-inflammatory activity [8].…”
Section: Various Uses Of Modified Immunoglobulins In the Treatment Ofmentioning
confidence: 99%
“…In addition, pathogenic autoantibodies contribute significantly to antibody-initiated inflammation in RA progression. Targeting IgG by glyco-engineering bacterial enzymes to specifically cleave IgG and alter N-linked Fc-glycans or blocking the downstream effector pathways offers a novel opportunity to develop therapeutics for RA treatment in the future [135]. Novel drugs targeting IL-12/IL-23 axis have been proven effective in the treatment of severe psoriasis and psoriatic arthritis (i.e., ustekinumab targeting the IL-12/23 p40 subunit that inhibits IL-12 and IL-23 activity and guselkumab targeting IL-23) [136].…”
Section: Clinical Trials and The Spotlight For Ra In The Futurementioning
confidence: 99%